Pelabelan Antiajaib Berdasarkan Jarak pada Operasi Perkalian Tensor Graf - Christyan Tamaro Nadeak (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
Let  be a graph of order n. Let  be a bijection. For any vertex , the neighbor sum  is called the weight of the vertex  and is denoted by where N(v) is the open neighborhood of If  for any two distinct vertices  and then f is called a distance antimagic labelling. If the graph G admits such a labelling, then G is said to be a distance antimagic graph. This study gives a distance antimagic labelling for tensor product of two complete graph and sufficient condition so that the tensor product of a regular graph and complete graph is a distance antimagic graph.